Sinonasal Inflammation or Neoplasm: Raise the Red Flagsǃ—A Pictorial Review - Kumar, Jyoti; Daga, Radhika; Pradhan, Gaurav; Meher, Ravi (Indian Journal of Radiology and Imaging, 2023)
Inflammatory pathology remains the most common indication for sinonasal imaging. However, sinonasal region is also the epicenter of a variety of neoplasms. These are often missed both clinically and radiologically owing to nonspecific signs and symptoms and subtle imaging pointers. An early diagnosis of sinonasal neoplasms is critical for timely management and hence better prognosis and survival rate.This pictorial review aims to acquaint the reader with the “red flag” signs on computed tomography that should raise suspicion for an underlying neoplastic pathology and also highlights the imaging features of common sinonasal neoplasms.
Keywords: chronic sinusitis; sinonasal neoplasms; red flags; CT